IMPLEMENTASI NINE STEP METHODOLOGY DALAM PERANCANGAN DATA WAREHOUSE - Atmojo, Wahyu Tisno; Ocktavia, Shabila; Ayunda, Afifah Trista (STMIK Sinar Nusantara, 2024)
Rapid technological developments require companies to create information systems that can organize and process company information effectively and efficiently. PT. Universal Karya Jaya is a company engaged in metal cutting services. The company does not have a running Information System yet. Therefore, it is necessary to have a good information system to support its business processes through data warehouse design. The design of the data warehouse uses the nine- step methodology from Kimball and uses star modeling so that PT. Universal Karya Jaya can make their company data integrated and help superiors analyze data for fast and accurate decision making. The goal to achieve from this research is to design a data warehouse model that suits the needs of the company and it is hoped that this design can be implemented at PT. Universal Karya Jaya to support their business processes. Meanwhile, the research method used for this research was literature study and interviews. With this data warehouse, it is hoped that it can assist companies in handling large amounts of data so that it can become a helping hand on inputs for stakeholders in the decision-making process.